PERAN IMIGRASI KELAS 1 KOTA MALANG DALAM MENANGANI TENAGA KERJA INDONESIA ILEGAL (SELUNDUPAN NON PROSEDURAL) (Studi Pada Kantor Imigrasi Kelas 1 Kota Malang) - Mahmud Aprian Mabruri; Midkholus Surur; Yendra Erison; Alif Firdaus Zam Zam; M Nizam Ardiansyah (Universitas Islam Darul Ulum Lamongan, 2023)
This research aims to find out and analyze the role of Class I Immigration in Malang City in terms of its services to help handle and prevent Indonesian workers or what are usually called TKI from being illegally smuggled non-procedurally. Around 3 thousand Malang City residents leave every year to become Indonesian Migrant Workers (PMI) to the Asia Pacific region. This figure is data officially written at the Malang City Manpower Service (Disnaker). Meanwhile, for non-procedural or illegal PMIs which are managed by Private Indonesian Migrant Worker Placement Implementers (PPTKIS) outside the region or fake ones. This research uses the Qualitative Descriptive Method and adopts analysis from the New Public Management Theory in the services provided and determines the role of Class I Immigration in Malang City. From this research, the results were obtained and that the services provided were good in accordance with the applicable SOP, but the obstacles that occurred lay in the individual members of the community who would become migrant workers. It is hoped that in the future the Class I Immigration of Malang City will be able to more discipline in examining documents that are prone to being fake and the need for cross-sector integration between several related agencies or departments in carrying out their duties. No less important is socializing the dangers of illegal migrant workers to the public in order to raise public awareness of the process of becoming Indonesian workers.